2023
DOI: 10.1177/14799731231163874
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cognitive capacity on physical performance in chronic obstructive pulmonary disease patients: A scoping review

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is often accompanied by impaired cognitive and physical function. However, the role of cognitive function on motor control and purposeful movement is not well studied. The aim of the review was to determine the impact of cognition on physical performance in COPD. Methods: Scoping review methods were performed including searches of the databases: MEDLINE, EMBASE, Cochrane Systematic Reviews, Cochrane (CENTRAL), APA PsycINFO, and CINAHL. Two reviewers inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 112 publications
0
6
0
Order By: Relevance
“…There is also evidence from our group that loss of neural automaticity may be an underlying mechanism contributing to slower gait speed among individuals with COPD [ 11 ]. Collectively, these changes suggest that cognitive limitations may arise from increased attentional demands and neural inefficiency, which may contribute to decreased cognitive and physical performance in COPD [ 17 ]. Although traditional pulmonary rehabilitation does not appear to improve dual task gait in patients with COPD [ 15 ], cognitive training is known to produce distinct benefits on dual task reaction time [ 61 ] and has been shown to independently improve measures of functional mobility among healthy older adults [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also evidence from our group that loss of neural automaticity may be an underlying mechanism contributing to slower gait speed among individuals with COPD [ 11 ]. Collectively, these changes suggest that cognitive limitations may arise from increased attentional demands and neural inefficiency, which may contribute to decreased cognitive and physical performance in COPD [ 17 ]. Although traditional pulmonary rehabilitation does not appear to improve dual task gait in patients with COPD [ 15 ], cognitive training is known to produce distinct benefits on dual task reaction time [ 61 ] and has been shown to independently improve measures of functional mobility among healthy older adults [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dual task decrements (difference between dual and single task performance) are often more pronounced in those with existing cognitive impairments or neurological conditions compared with those without these disorders [ 13 , 14 ]. Indeed, increased dual task decrements for both motor [ 12 , 15 ] and cognitive [ 16 ] performance have been found among people with COPD compared with healthy individuals [ 17 ]. There is emerging evidence indicating that cognitive-motor dual task performance impairment among patients with COPD is related to alterations in markers of prefrontal cortex neural activity and inefficiency, which may impede the executive function needed to plan one’s day [ 11 , 12 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that ILD exacerbations and hospitalizations are a significant source of morbidity and mortality ( 28 , 30 , 32 , 34 , 54 - 57 ), identification of frailty parameters that are potentially modifiable such as weight loss, skeletal muscle dysfunction, and physical activity should be important considerations in the management of ILD patients ( 56 , 57 ). In addition, the concept of cognitive impairment and interference is gaining increased recognition in the COPD literature ( 176 ), with a few studies now highlighting cognitive limitations in ILD. Thus, modifiable risk factors that can limit cognition, such as hypoxemia and dyspnea, need to be addressed by use of supplemental oxygen, increasing fitness, and utilization of energy conservation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Many daily activities involve the simultaneous accomplishment of cognitive and motor tasks, known as cognitive-motor dual-task situations (CMDT) such as talking while walking or identifying the front door key on a key ring while climbing the stairs. Although few studies have focused on the concept of dual tasks in pwCOPD (for review, see Rassam et al 2023), they agree that patients have insufficient attentional resources to successfully perform both tasks simultaneously compared to healthy controls, exhibiting thus a higher dual-task interference. For instance, Morlino et al (2017) showed that the time to perform Timed Up and Go test (a basic functional mobility test) increased to a greater extent from the single-task to the dual-task condition in pwCOPD compared to healthy controls.…”
Section: Introductionmentioning
confidence: 99%